2015
DOI: 10.1007/s13197-015-1942-9
|View full text |Cite
|
Sign up to set email alerts
|

Citrus peel extract incorporated ice cubes to protect the quality of common pandora

Abstract: The objective of this study was to investigate the effects of ice with albedo and flavedo fragments of Citrus (Grapefruit (Citrus paradisi) and Bitter orange (Citrus aurantium L.)) extracts on the quality of common pandora (Pagellus erythrinus). Concentrated citrus extracts were diluted with distilled water (1/100w/v) before making of ice. The ice cubes were spread on each layer of fishes and stored at 0°C for 15 days. The pH value showed a regular increase in all samples. TVB-N levels of bitter orange treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Albedo and flavedo fragments of grapefruit and bitter orange extracts incorporated in to ice cubes were found effective on biochemical changes of common pandora ( Pagellus erythrinus ) stored with this ice …”
Section: Plant‐based Preservativesmentioning
confidence: 99%
“…Albedo and flavedo fragments of grapefruit and bitter orange extracts incorporated in to ice cubes were found effective on biochemical changes of common pandora ( Pagellus erythrinus ) stored with this ice …”
Section: Plant‐based Preservativesmentioning
confidence: 99%
“…TBARS were determined according to Yerlikaya et al (2015) to evaluate the oxidation stability during chilled storage and the results were expressed as TBARS value in mg of malonaldehyde per kg (mg MDA kg -1 ) of fish sample.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars)mentioning
confidence: 99%
“…However, they also expressed a bitter taste in the samples treated with this amount of extract. In another study, addition of citrus peel extracts into ice during cold storage of common carp suppressed secondary lipid oxidation products in comparison to the control (Yerlikaya et al, 2015). It was also reported that the rancidity development remained low in pink salmon stored in iced or chilled sea water.…”
Section: Quality Assessmentmentioning
confidence: 90%
“…There are studies that have added plant extracts to ice in order to examine the chemical quality of fish (Quitral et al, 2009;Yerlikaya, Ucak, Gumus & Gokoglu, 2015) or to create a biofilm (Bensid, Bendeddouche, Toy, Sigirci & Özogul, 2014a). However, it is also important to examine the effect of extract on the taste and appearance of fish in terms of consumer acceptance.…”
Section: Introductionmentioning
confidence: 99%